Imaging DNA damage allows detection of preneoplasia in the BALB-neuT model of breast cancer. - Cornelissen, B; Able, S; Kartsonaki, C; Kersemans, V; Allen, P; Cavallo, F; Cazier, J; Iezzi, M; Knight, J; Muschel, R; Smart, S; Vallis, K (Society of Nuclear Medicine, 2014)
A prominent feature of many human cancers is oncogene-driven activation of the DNA damage response (DDR) during early tumorigenesis. It has been shown previously that noninvasive imaging of the phosphorylated histone H2A variant H2AX, γH2AX, a DNA damage signaling protein, is possible using (111)In-labeled anti-γH2AX antibody conjugated to the cell-penetrating peptide transactivator of transcription (TAT). The purpose of this study was to investigate whether (111)In-anti-γH2AX-TAT detects the DDR during mammary oncogenesis in BALB-neuT mice.Mammary fat pads from BALB-neuT and wild-type mice (age, 40-106 d) were immunostained for γH2AX. (111)In-anti-γH2AX-TAT or a control probe was administered intravenously to BALB-neuT mice. SPECT was performed weekly and compared with tumor detection using palpation and dynamic contrast-enhanced MR imaging.γH2AX expression was elevated in hyperplastic lesions in the mammary fat pads of BALB-neuT mice aged 76-106 d, compared with normal fat pads from younger mice and carcinomas from older mice (13.5 ± 1.2 γH2AX foci/cell vs. 5.2 ± 1.5 [P < 0.05] and 3.4 ± 1.1 [P < 0.001], respectively). Serial SPECT imaging revealed a 2.5-fold increase in (111)In-anti-γH2AX-TAT accumulation in the mammary fat pads of mice aged 76-106 d, compared with control probe (P = 0.01). The median time to detection of neoplastic lesions by (111)In-anti-γH2AX-TAT (defined as >5% injected dose per gram of tissue) was 96 d, compared with 120 and 131 d for dynamic contrast-enhanced MR imaging and palpation, respectively (P < 0.001).DDR imaging using (111)In-anti-γH2AX-TAT identified mammary tumors significantly earlier than MR imaging. Imaging the DDR holds promise for the detection of preneoplasia and as a technique for screening cancer-prone individuals.